Rapid identification of chemical components in Xuelian granule by UHPLC-Q-orbitrap-HRMS based on enzyme activity in vitro - Xiatiguli Taximaimaiti; Rahima Abdulla; Xuelei Xin; Yuan Zhao; Yi Liu; Haji Akber Aisa; Deqiang Deng; Tao Wu (BMC, 2023)
Abstract Background Xuelian granule (XL), a traditional Chinese medicine (TCM) formula, has been used for the treatment of diabetic nephropathy for a long time as a hospital preparation. Because the active ingredients in the XL that can help to treat diabetic nephropathy are still unclear, which limits the interpretation for its pharmacological mechanism, further development and subsequent study on the material basis of its efficacy. Methods In this study, a screening method based on inhibition activity against aldose reductase (AR) was employed for activity-directed chemical analysis of XL using ultra-high performance liquid chromatography combined with quadrupole-orbitrap high resolution mass spectrometry (UHPLC-Q-orbitrap-HRMS) technique. Results A total of 178 compounds, including 46 terpenes, 47 organic acids, 25 flavonoids, 29 phenylethanoid glycosides, and 31 other types, were tentatively identified from XL which might responsible for its AR inhibition activity. Conclusion This is the first study for a systematic, rapid, and accurate qualitative analysis of XL. This research provides a scientific and experimental basis for further researches on pharmacodynamics material basis and quality control of XL.